Análise histopatológica e resposta inflamatória das lesões com dermatite atópica em camundongos induzidas por calcipotriol e tratadas com e-caderina recombinante - Ribeiro, Laura Alves (2019)
Atopic dermatitis (AD) is a chronic and multifactorial disease characterized by the presence of inflammatory infiltrates, epidermal hyperplasia and dysfunction in the epithelial barrier. The susceptibility of the epithelial barrier allows the entry of allergens that activate Th2 profile cells and increase the levels of IgE in the acute phase. This study aimed to induce AD-like lesions at the ear of BALB/c mice by calcipotriol (CPT) and treat them recombinant mouse e-cadherin (rmE-cad). AD-like lesions were induced by topical (ear) application of CPT in a volume of 20 μl during 28 days and it was performed by using four different groups, with four animals each, for standardization: Group 1: 1 pmol of CPT, Group 2: 4 pmols of CPT, Group 3:1 pmol of CPT + Ovalbumin (OVA), and Group 4: 4 pmols of CPT + OVA. The optimal concentration of CPT for induction of AD in this study was 4 pmols (Group 2), leading to acute AD-like lesions with a significant increase in the total serum IgE, total tissue IgE and tissue IL-5 levels in comparison with other groups (Groups 1 and 3). Thus, the Group 2 was chosen for treatment with 0.5 μg/ml, 1 μg/ml or 2 μg/ml of rmE-cad. Topical application of 2 μg/ml of e-cadherin demonstrated evident clinical improvement as well as a significant decrease in the total serum IgE and total tissue IgE, tissue IL-5 and tissue TSLP levels, with an increase in the levels of the tissue IL-10 cytokine in comparison with other treated groups. In conclusion, this study demonstrated that the best concentration of CPT for induction of experimental murine AD was 4 pmols/20μl and the optimal dosis of e-cadherin for treatment was 2 μg/ml, improving both clinical and immunological parameters, by decreasing tissue inflammatory factors as well as by increasing IL-10 regulatory cytokine.